Origin of romantic fiction - Adams, Emory Sherwood (My University, 1898)
Introduction: Fabulous narrative, like almost every one of the arts of man, originated in the desire of rendering the great more vast, the rich more splendid, and the gay more beautiful. It removed, as it were, from the hands of fortune, the destinies of mankind, rewarded virtue and valor with success, and covered treachery and baseness with opprobrium.
Citation: Adams, Emory Sherwood. Origin of romantic fiction. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Narrative; Fortune; Mankind; Theses; Manuscripts (documents)